# The HCF of 65 and 117 is expressible in the form 65m-117.Find the value of m. Also find the LCM of 65 and 117 using prime factorisation method.

let us find the HCF of 65 and 117,

117 = 1×65 + 52

65 = 1× 52 + 13

52 = 4 ×13 +0

therefore HCF of 65 and 117 is 13.

65m-117 = 13

65m = 117+13 = 130

m =130/65 =2

Now, 65 = 5 × 13

117 = 13 × 3 × 3

LCM of 65 and 117 = 5 × 13 × 3 × 3 = 585

• 134
Among 65 and 117; 117 > 65
Since 117 > 65, we apply the division lemma to 117 and 65 to obtain
117 = 65 × 1 + 52 … Step 1
Since remainder 52 ≠ 0, we apply the division lemma to 65 and 52 to obtain
65 = 52 × 1 + 13 … Step 2
Since remainder 13 ≠ 0, we apply the division lemma to 52 and 13 to obtain
52 = 4 × 13 + 0 … Step 3
In this step the remainder is zero. Thus, the divisor i.e. 13 in this step is the H.C.F. of the given numbers
The H.C.F. of 65 and 117 is 13

From Step 2:
13 = 65 – 52 × 1 … Step 4
From Step 1:
52 = 117 – 65 × 1
Thus, from Step 4, it is obtained
13 = 65 – (117 – 65 × 1) × 1
⇒13 = 65 × 2 – 117
⇒13 = 65 × 2 + 117 × (–1)
In the above relationship the H.C.F. of 65 and 117 is of the form 65m + 117 n, where m = 2 and n = –1

65=5*13
117=3*3*13
LCM(65,117)=5*3*3*13
=585
• 16

Among 65 and 117; 117 > 65

Since 117 > 65, we apply the division lemma to 117 and 65 to obtain
117 = 65 * 1 + 52 … Step 1
Since remainder 52 ≠ 0, we apply the division lemma to 65 and 52 to obtain
65 = 52 * 1 + 13 … Step 2
Since remainder 13 ≠ 0, we apply the division lemma to 52 and 13 to obtain
52 = 4 * 13 + 0 … Step 3
In this step the remainder is zero. Thus, the divisor i.e. 13 in this step is the H.C.F. of the given numbers
The H.C.F. of 65 and 117 is 13

From Step 2:
13 = 65 – 52 * 1 … Step 4
From Step 1:
52 = 117 – 65 * 1
Thus, from Step 4, it is obtained
13 = 65 – (117 – 65 * 1) * 1
⇒13 = 65 * 2 – 117
⇒13 = 65 * 2 + 117 * (–1)
In the above relationship the H.C.F. of 65 and 117 is of the form 65m + 117 n, where m = 2 and n = –1

65=5*13
117=3*3*13
LCM(65,117)=5*3*3*13
=585
• 4
What are you looking for?